A paper-based device for glyphosate electrochemical detection in human urine: A case study to demonstrate how the properties of the paper can solve analytical issues - Giulia Moro; Francesco Fama; Noemi Colozza; Andrea Gambaro; Marco Bassanello; Fabiana Arduini; Chiara Zanardi (Green Analytical Chemistry, 2023)
In the ever-growing demand for agricultural production, the use of pesticides and the consequential health risks is an issue that remains in the spotlight. The biomonitoring of pesticides in biological matrices is a mandatory task to point out the adverse effects on those people that are particularly exposed (i.e., occupational exposure) and to customize the use of pesticides for safer and more aware agricultural practices (i.e., precision agriculture). To overcome the bottleneck of costs and long sample treatments, we conceived a paper-based analytical device for the fast and smart detection of glyphosate in human urines, which is still the most widespread pesticide. Importantly, we demonstrate how to face the analytical interference given by uric acid to develop an electrochemical sensor for glyphosate detection using paper as a multifunctional material. To this purpose, a sample treatment was pointed out and integrated into a paper strip to decrease the level of uric acid in urines, finally delivering a ready-to-use device that combines lateral and vertical flow. The effective decrease of uric acid after the paper-integrated treatment is verified by direct oxidation in differential pulse voltammetry, whereas glyphosate detection can be carried out by enzyme inhibition assay in chronoamperometry. The system showed a limit of detection for glyphosate of 75 μg/L and a linear range of 100 - 700 μg/L. Additionally, the sustainability of the paper device was assessed and compared with reference chromatographic methods. Overall, this work provides an example of how to design green sensing solutions for addressing analytical challenges in line with the White Analytical Chemistry principles.